Strategi visual branding dalam meningkatkan minat beli ulang Mie Balap Mak Nong di Kota Langsa - Aditya, Dimas; Sumarni, Mutia; Sari, Juli Dwina Puspita; Chalil, Rifyal Dahlaway (Nur Science Institute, 2024)
This research aims to determine the visual branding strategy used by Mie Balap Mak Nong to increase buyers' repurchase interest. This method uses field research, which uses a descriptive qualitative approach. The research subjects comprised five community informants, one key informant from the Mak Nong racing noodle business owner and one key informant from an employee. The sampling method uses the snowball sampling technique. Research data sources consist of primary and secondary data. The research results show that Mie Balap Mak Nong has succeeded in developing its products with a visual branding strategy, improving quality, and maintaining authentic taste based on the tastes of modern consumers. Collaboration with Lokerlangsa and utilization of WhatsApp increasing brand visibility. Responsive packaging changes demonstrate a commitment to innovation, illustrating the brand's continued development. Mie Balap Mak Nong's visual branding is important in attracting and maintaining consumer interest.